Development of the Institution of Citizenship of the Republic of Abkhazia as a New Subject of International Law - I. N. Bartsits (Московский журнал международного права)
The article reviews the development of the institution of citizenship in the Republic of Abkhazia as a new subject of International law. The recognition by the Russian Federation made on August 26, 2008 has become the key element of establishing its international subjectivity of the Republic of Abkhazia.The legal institute of citizenship of the Republic of Abkhazia is developing since the demise of the Soviet Union when Abkhazia declared its sovereignty and afterwards – independence, through the period of successful for Abkhazia war with Georgia (1992-1993).Sustaining that the main problem for legal regulation of citizenship is the issue of double citizenship and its recognition, the article analyzes legislative and political aspects of the problem. A particular attention is paid at scrutinizing the issue of double citizenship as regulated by the Treaty of Friendship, cooperation and mutual assistance between the Russian Federation and the Republic of Abkhazia.